2009
DOI: 10.1002/chem.200901521
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dependence of σ‐Electron Delocalization in Linear Chains: Permethylated Oligosilanes

Abstract: The effects of sigma-electron delocalization on optical properties of saturated linear chains of permethylated oligosilanes are strongly conformation dependent. We analyze the origin of the conformational dependence of the energies of molecular orbitals and of electronic excitations in simple intuitively understandable terms by using a first-order approximation to the Hückel version of the "Ladder C" model. The analysis is supported by comparison with results of numerical calculations from time-dependent densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 81 publications
2
89
0
Order By: Relevance
“…In oligosilanes with a non-planar skeleton of silicon atoms excited states of strongly mixed nature are also possible but are relatively rare. This is especially true in the alltransoid conformers, whose silicon skeleton is almost planar and the σσ*, σπ* nomenclature quite satisfactory 10 . The lowest σ* and π* MOs in peralkylated oligosilanes are of comparable energy and one or the other is the lowest unoccupied molecular orbital (LUMO).…”
Section: Molecular Orbitals and Excited States In Saturated Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…In oligosilanes with a non-planar skeleton of silicon atoms excited states of strongly mixed nature are also possible but are relatively rare. This is especially true in the alltransoid conformers, whose silicon skeleton is almost planar and the σσ*, σπ* nomenclature quite satisfactory 10 . The lowest σ* and π* MOs in peralkylated oligosilanes are of comparable energy and one or the other is the lowest unoccupied molecular orbital (LUMO).…”
Section: Molecular Orbitals and Excited States In Saturated Systemsmentioning
confidence: 98%
“…Although all valence excitation in saturated systems without lone pairs, such as the oligosilanes, necessarily is from bonding orbitals of σ type to antibonding orbitals of σ* type, it is useful to distinguish two types of delocalized molecular orbitals (MOs) in an oligosilane chain 6,10 . Those that are symmetric with respect to the local Si-Si-Si plane are said to be of local σ character and those that are locally antisymmetric, of local π character.…”
Section: Molecular Orbitals and Excited States In Saturated Systemsmentioning
confidence: 99%
“…The coupling, however, could be lifted through rotation of the fragments against each other as has been, e.g., analyzed before in the context of  electron delocalization in permethylated oligosilanes. [29] There, it was shown by a theoretical rationalization that occupied and unoccupied orbitals with  bond character and hence * excitations depend strongly on the dihedral angles along the bonds separating two identical polysilane fragments. Two aspects from that piece of research find their counterparts here: rotation effects and orbital splitting.…”
Section: Ii3 Biuretmentioning
confidence: 99%
“…Other models, such as Sandorfy H, account for the LUMO, focusing on the interaction between the backbone and substituent orbitals [13]. Elaborations on these descriptive models have shown that the simple intuitions of HMO theory still hold [30]. By employing ab initio methods such as DFT where the effective core potentials of tin are accounted for, structure predictions can be made without the requirement of existing experimental data [31].…”
mentioning
confidence: 99%